Host-Parasite Relationships in Porcine Ascariosis: Anticoagulant Potential of the Third Larval Stage of Ascaris suum as a Possible Survival Mechanism - Diosdado, Alicia (Animals (Basel), 2021)
SIMPLE SUMMARY: Ascaris suum parasitises pigs all over the world causing a disease responsible for producing reductions in weight gains and damages to several organs of the infected animals that incur huge economic losses for the swine industry. While adult worms of this parasite are located in the small intestine of the host, their larval stages migrate through the bloodstream as an evolutionary advantageous strategy within a hostile environment that confronts host responses such as blood clots formation. The aim of this work is to study the ability of A. suum larvae to inhibit blood coagulation as a possible mechanism to control blood clots formation and facilitate their migration. The results showed that these larvae inhibited host blood coagulation and possessed molecules similar to those responsible for inhibiting blood coagulation in pigs. The anticoagulant effect of A. suum larvae could constitute a potential survival mechanism for the parasite. Therefore, developing new control strategies directed at this and similar processes could avoid A. suum larval migration and the establishment of adult worms in their definitive location, which is necessary to confront the damages and economic losses produced by this parasitosis. ABSTRACT: In order to evade the response of their hosts, helminth parasites have evolved precise and highly regulated mechanisms, including migration strategies of the larval stages. In regard to porcine ascariosis caused by Ascaris suum, its infective third-stage larvae (AsL3) undergo a complex migratory route through the bloodstream of their host before establishing in the small intestine to reach maturation. Despite the benefits attributed to this migration, blood clots formation could compromise larvae survival. The aim of this work was to study the interaction between the cuticle and excretory/secretory antigens of AsL3 and the host coagulation cascade. Larvae were obtained after incubating and hatching A. suum eggs, after which the antigenic extracts were produced. Their ability to disrupt the coagulation cascade was studied using anticoagulation and chromogenic assays, and techniques based on electrophoresis. The obtained results showed that both antigenic extracts possessed anticoagulant potential, being able to inhibit the intrinsic, extrinsic and/or common pathways of the blood coagulation cascade as well as the activated factor X. Moreover, three A. suum serpin proteins were identified as candidates to inhibit this host coagulation factor. To the best of our knowledge, this study shows, for the first time, the anticoagulant potential of the infective larvae of A. suum, which could be used by the parasite as a mechanism to facilitate its invasion and survival in the host.